THE ROLE OF CONCENTRATION IN PREDICTING PROCRASTINATION IN QUR’ANIC MEMORIZATION AMONG UNIVERSITY STUDENTS: A CORRELATIONAL STUDY - Indri Puspitasari; Shalahudin Habibullah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Procrastination remains a persistent challenge in higher education, particularly among students managing demanding learning commitments. Within religious memorization contexts such as Qur’anic study, sustained concentration is essential for effective encoding, retention, and timely completion of memorization targets. However, limited empirical research has examined how attentional capacity relates to procrastination behavior in faith-based academic environments. This study investigates whether concentration ability predicts procrastination in Qur’anic memorization among university students engaged in structured religious learning programs. It specifically examines the direction and strength of the relationship between these two variables. A quantitative correlational design was employed. Participants consisted of 18 university students enrolled in Qur’anic memorization programs. Data were collected using two Likert-type scales: a concentration scale adapted from Castle and Buckler’s theoretical framework and a procrastination scale based on Ferrari’s model. After item validation and reliability testing (Cronbach’s alpha = 0.859 for concentration; 0.877 for procrastination), data were analyzed using Spearman’s rho due to non-linearity assumptions. Descriptive, normality, and linearity tests preceded hypothesis testing. The findings revealed a significant negative correlation between concentration and procrastination (r = –0.636, p = 0.005). Higher concentration was associated with lower levels of procrastination in Qur’anic memorization tasks. These results underscore concentration as a critical cognitive factor in reducing avoidance behaviors within structured religious learning contexts. The study highlights the importance of strengthening attentional regulation strategies to support students managing dual academic and memorization demands. Although limited by sample size, the findings contribute to educational psychology by extending procrastination research into faith-based learning environments and suggest practical implications for instructional design and mentoring practices aimed at enhancing student self-discipline and academic persistence. ABSTRAK Prokrastinasi merupakan tantangan yang sering ditemui pada mahasiswa dalam konteks pembelajaran. Dalam lingkungan hafalan Al-Qur’an, konsentrasi menjadi faktor kognitif penting karena penghafalan memerlukan fokus yang berkelanjutan dan ketahanan mental. Meskipun penelitian mengenai prokrastinasi akademik telah banyak dilakukan, kajian yang meneliti peran konsentrasi dalam hafalan Al-Qur’an masih terbatas. Penelitian ini bertujuan untuk menguji apakah konsentrasi dapat memprediksi prokrastinasi pada mahasiswa yang mengikuti program hafalan Al-Qur’an. Menggunakan pendekatan kuantitatif dengan desain korelasional, penelitian ini melibatkan 18 mahasiswa aktif dalam program hafalan Al-Qur’an. Instrumen yang digunakan adalah skala konsentrasi dan prokrastinasi yang dikembangkan berdasarkan teori Castle dan Buckler serta model Ferrari. Hasil analisis dengan uji Spearman rho menunjukkan korelasi negatif signifikan antara konsentrasi dan prokrastinasi (r = -0,636; p = 0,005), yang berarti semakin tinggi konsentrasi mahasiswa, semakin rendah kecenderungan prokrastinasi. Temuan ini menegaskan pentingnya konsentrasi dalam mengurangi prokrastinasi dalam pembelajaran berbasis hafalan. Penelitian ini memperluas kajian prokrastinasi ke dalam konteks pendidikan berbasis religius, memberikan kontribusi pada pengembangan strategi pembinaan yang berfokus pada penguatan kapasitas atensi mahasiswa..